ANALISIS ETIKA KEGURUAN DALAM MENCIPTAKAN SUASANA BELAJAR YANG MENYENANGKAN DALAM PROSES PEMBELAJARAN DI SMA NEGERI 5 MEDAN - Hartika, Dewi; Sitorus, Kapita; Regar, Nisa Andriani; Yunita, Sri (Universitas Methodist Indonesia, 2023)
Education plays a significant role in shaping the character of students through a learning process that involves knowledge, understanding, and information conveyed by educators. Teacher ethics play a crucial role in ensuring quality education. As a teacher, creating an engaging and stimulating learning environment is essential to enhance student motivation and engagement in the learning process. This research adopts a descriptive method with a qualitative approach conducted at SMA Negeri 5 Medan. Data were collected through individual behavior observation and interviews with PPKn teachers. PPKn teachers are expected to possess skills such as effective questioning, providing motivation, classroom management, and creating learning variations. Various teaching methods utilized by PPKn teachers to create an interesting learning atmosphere include role play, group discussions, and the use of digital media. Learning while playing can assist students in better understanding and absorbing the learning materials.